A legislação brasileira e italiana sobre Educação Especial : da década de 1970 aos dias atuais - Cabral, Leonardo Santos Amâncio (Universidade Federal de São Carlos, 2010)
The opinions of several countries on how to enforce the education of people with disability promote international discussions aimed at identifying elements, whether from the political, organizational or methodological sphere, that can solve the existing problems in their respective educational contexts. Essentially, there are countries which provide education only in specialized centers, such as Ireland, or predominantly in the classrooms of the regular school system, such as Italy, or like a continuum of services, with the establishment of a partnership between the regular school system and the specialized centers, such as Brazil, predominantly. With that in mind, and considering the current inclusive perspective of Special Education in our country and discussions that tend to defend the inclusion of all students in common classes of regular school, we saw the need to investigate how the educational services to people with disability is organized in Italy, since this is the country that, almost forty years ago, have established the school inclusion which is considered by many the most radical one. To do so, we have chosen to develop a comparative study on legislation of Special Education in Brazil and Italy, through the study of official documents, following a specific protocol, such as constitutions, laws, decrees and resolutions, taken place between the 1970s and 2009, which dealt with issues related to persons with disabilities. So, this is a documentary study, having content analysis as the main approach. It has been presented, at the beginning, a brief history of special education concerning the two countries until the 1970s and we have also made an effort to contextualize them in relation to social-economic and educational characteristics, and we have also differentiated the concepts of integration and inclusion for both countries and the criteria for identifying people with special educational needs. In the next section, we have presented, analyzed and discussed the data identified for each country. We have concluded, from the comparative perspective, that: 1) while Brazil establishes legal mechanisms to encourage changes, in Italy, the standards are drawn up collectively to support existing practices; 2) the medical perspective to the identification of Special Education students in Italy decreases the population to be served to 1.5%, which in Brazil is estimated at 14.5%, which directly influences the targeting of investments in education for this particular segment, among other services; 3) while the Italian families claimed the education of their children in public spaces of society, in Brazil, the fight was for the operation of specialized institutions. However, despite the fact that inclusive education in Italy is considered the most radical one, it still recognizes the need to maintain the operation of specialized institutions for the deaf and blind; 4) in both contexts one can identify difficulties of coordination between health services and education; and 5) there is a common trend in the common classroom teachers to delegate the disabled student to a specialized teacher. Finally, considering that the comparison with another country makes us reflect on our own practices, the study allowed us considerations about the current speech of radical inclusion that permeates the brazilian educational policy and we have seen, when considering the Italian experience, that many problems have not yet been solved in that context, which may indicate that the path of radicalization of school inclusion may not be necessarily the one Brazil should take. Instead, we should, rather than coming up with new laws, effectively implement the existing ones, respecting the rights of disabled people.
Keywords: Educação especial; Inclusão escolar; Estudo comparativo; Brasil - Itália; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL